Pengaruh Adaptasi Teknologi dan Pelatihan Pengemudi Terhadap Kinerja Pengemudi Ojek Online di Kota Palangka Raya - Muhammad Nurhasim; Rita Yuanita Toendan; Ani Mahrita; Hansly Tunjang (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of technology adaptation and driver training on the performance of online motorcycle taxi drivers in Palangka Raya City. Technology adaptation refers to drivers’ ability to adjust to the development of digital transportation applications, while driver training aims to improve the skills and competencies required to perform their duties effectively. This study employed a quantitative approach using an associative research method. The sample consisted of 101 online motorcycle taxi drivers selected through purposive sampling. Data were collected through questionnaires using a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The results indicate that technology adaptation does not have a significant effect on driver performance, with a t-statistic value of 1.583 and a p-value of 0.113. This finding suggests that the ability to use online transportation applications has become a basic requirement for drivers and is no longer a primary factor influencing performance. In contrast, driver training has a positive and significant effect on driver performance, with a t-statistic value of 4.466 and a p-value of 0.000. Furthermore, the R-Square value of 0.657 indicates that technology adaptation and driver training explain 65.7% of the variance in driver performance. The findings confirm that driver training is a more dominant factor in improving the performance of online motorcycle taxi drivers than technology adaptation.